ANALISA PUTUSAN HAKIM TERHADAP PENGEMUDI KENDARAAN BERMOTOR YANG KARENA KELALAIANNYA MENGAKIBATKAN ORANG LAIN MENINGGAL DUNIA - Yosephine Elizabeth; Inri Januar; Lonna Yohanes Lengkong (Fakultas Hukum Universitas Kristen Indonesia, 2023)
Traffic Accident is an incident on the streets that happened out of nowhere that can cause damage, injuries, and even death. The research problem of this thesis are to know the criminal liability of the act of Negligence Caused Death in Indonesian’s Law and the application of its criminal liability towards someone’s behavior of negligence caused death in the Medan District Court Verdict No: 3569/Pid.Sus/2021/PN Mdn). The research method that is used by the author is the method of normative juridical which uses case approach and statute approach. The data sources that is used by the author is the secondary data in which are primary materials, secondary materials, and tertiary material. For the outcome, the author concluded that the Prosecutors can’t proof the Defendant actions in details. In the Medan District Court Verdict No: 3569/Pid.Sus/2021/PN Mdn, there is nothing that can be use a proof or something that can be convincing enough to proof that the Defendant is indeed driven the Vehicle above the Speed Limit. So because of that, the Judges should’ve made the verdict as a free verdict.